Dealing with the Commonplace: Constantinos A. Doxiadis and the Zygos Technical Company - Konstantina Kalfa; Lefteris Theodosis (ABE Journal)
This paper deals with a largely unknown episode in the prolific career of the internationally renowned planner Constantinos A. Doxiadis (1913-1975). Between 1962 and 1974, he operated the construction company Zygos S.A. with a view to take advantage of the opportunities presented by the proliferation of the polykatoikìa (a characteristic mid-rise apartment building in Greece) via antiparochì (a popular land-for-flats contract)Αs this paper analyzes, the story of Zygos offers a unique opportunity to unpack a series of important issues regarding housing production and urbanization processes in postwar Greece—and potentially other countries—where housing was neither undertaken by centralized mechanisms, nor promoted by the welfare state. It discusses how the self-propelling mechanism of antiparochì both created and drew on a system of social and economic interdependencies that enjoyed broad support across the political spectrum, while boosting the growth of a speculative real estate market, where amateurish contractors and small construction companies thrived. In fact, the growth of such a market owes a lot to the regulatory measures launched by Doxiadis while being in charge of the Greek Reconstruction and Recovery programs (1945-1951). Altogether, the story of Doxiadis’s involvement in the Greek real estate market offers a striking example of how top-down incentives and bottom-up initiatives converged to create the conditions and framework within which Greek architects (including renowned ones) routinely operated. To contextualize the design and building process of polykatoikìes (a commonplace building type outside the realm of high architectural design), the paper draws on the concept of the “commonplace” as an umbrella term used to describe the socio-economic conditions evinced in the antiparochì mechanism and the everyday lived experience of a developing urban society.